2017
DOI: 10.1139/apnm-2016-0390
|View full text |Cite|
|
Sign up to set email alerts
|

Improvement of activity-related knee joint discomfort following supplementation of specific collagen peptides

Abstract: this article has been changed to the CC BY 4.0 license. The PDF and HTML versions of the article have been modified accordingly. Abstract:The aim of the study was to evaluate the use of specific collagen peptides in reducing pain in athletes with functional knee problems during sport. Athletic subjects (n = 139) with functional knee pain ingested 5 g of bioactive collagen peptides (BCP) or a placebo per day for 12 weeks. The primary outcome of the study was a change in pain intensity during activity, which was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 30 publications
3
62
0
3
Order By: Relevance
“…In addition, ingestion of EHC led to significantly higher plasma concentrations of glycine, proline and hydroxyproline compared to non-hydrolyzed collagen. Notably, these AAs have been connected with the potential beneficial effects of collagen supplementation on tendinopathy and articular joint pain experienced in both OA patients and athletes [7,8,9,10,11,12,13,14,21,22]. As net collagen synthesis is negative in OA patients, enhancing collagen synthesis has been proposed to help regeneration of cartilage [11,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, ingestion of EHC led to significantly higher plasma concentrations of glycine, proline and hydroxyproline compared to non-hydrolyzed collagen. Notably, these AAs have been connected with the potential beneficial effects of collagen supplementation on tendinopathy and articular joint pain experienced in both OA patients and athletes [7,8,9,10,11,12,13,14,21,22]. As net collagen synthesis is negative in OA patients, enhancing collagen synthesis has been proposed to help regeneration of cartilage [11,22].…”
Section: Discussionmentioning
confidence: 99%
“…Collagen is an abundant structural protein present in connective tissue. Besides its nutritional value as a protein source, dietary supplementation with collagen-derived peptide sources has been suggested to provide beneficial effects in patients with tendinopathy [5,6,7], chronic joint instability [8], osteoarthritis (OA) [3,9,10,11,12], and activity-related joint pain [13,14]. Thus, nutritional interventions focusing on increasing the amino acid (AA) components of collagen have been suggested to improve collagen synthesis of collagen-rich tissues such as ligaments and bones [5] and potentially slow the degenerative process in OA affected joints [11].…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, Pro-Hyp accounts for more than 50% of total collagen peptides in human plasma. Pro-Hyp enhances fibroblast growth on a collagen gel (Shigemura et al, 2009;2011) and production of glycosaminoglycans by fibroblasts and chondrocytes (Nakatani et al, 2009;Ohara et al, 2010), which partly explain the beneficial effects of collagen hydrolysates; improvement of wound healing (Sugihara et al, 2015) and skin (Proksch et al, 2014a,b) and joint conditions (Zdzieblik et al, 2017). However, collagen hydrolysates ingested comprised collagen peptides with an average molecular weight of 5000 Da and did not contain Pro-Hyp (Iwai et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, human trials have demonstrated that the daily ingestion of collagen hydrolysate improves osteoarthritis‐related symptoms and skin conditions after several weeks . Moreover, a combination of daily ingestion of collagen hydrolysate and resistance training for 12 weeks increases muscle strength in sarcopenic patients …”
Section: Introductionmentioning
confidence: 99%